Differentiation among various kinds of cheese by identification of casein using HPLC-chip/MS/MS - Franc, Martin; Krízek, Tomás; Coufal, Pavel; Stulík, Karel (Journal of separation science, 2010)
In proteomics, proteins can be identified by enzymatic cleavage of the target protein using an enzyme of the known specificity (primarily trypsin), sequencing the obtained specific peptides by MS and comparing the amino acid sequence of the peptides with a protein database. The sophisticated approach described above was used in this study to determine and verify the original species of cheeses. Proteins were extracted from three different cheese samples which were produced from cow, sheep and goat milks. The isolated proteins were cleaved with trypsin and the peptides obtained were sequenced and identified by a HPLC-chip/MS/MS microfluidic system. Two different extraction methods and two various chromatographic sorbents packed in plastic chips were studied. Beta-lactoglobulin and four kinds of casein were found in the cheese samples. The species of kappa-casein were identified unambiguously in all the three cheese samples and, thus, kappa-casein can be used to determine the origin of milk of the cheese. The other proteins found in the samples show very similar primary structures and cannot be recommended for identification of the cheese milk origin.
Keywords: kaseiny; Caseins; vysokoúčinná kapalinová chromatografie; sýr; Chromatography, High Pressure Liquid; tandemová hmotnostní spektrometrie; Cheese; Tandem Mass Spectrometry